INFLUENCE OF A SYNCHRONIZED HUMAN DYNAMIC LOAD ON VIBRATIONS OF MACHINE STRUCTURES - Radoicic, Goran Nikola; Jovanovic, Miomir (Journal of Applied Engineering Science, 2021)
This paper contributes to the research of rhythmic behavior of a group of people, which, more or less synchronized, moves or jumps on a thin and elastic plate, thus performing a dynamically variable load. The analysis of the rhythmic behaviour of the crowd carried out on the basis of the experimental testing on the special steel test platform. The experiment consisted of sixteen measurements of live force and acceleration of the test platform. The dynamic loads caused by the mass of the human crowd and individuals had different intensities. The measurements of acceleration of the carrying platform were performed in order to estimate how the live human force influences on vibrations of machine structures. This research allows us to gain a picture of how serious the threats are from some human actions on the support structure of machines that are handled when performing works in industry, construction or mining. On the basis of these experiments, the mathematical models of the equivalent excitation forces were developed. The measured accelerations of the test platform tread surface and calculated dynamic coefficients of human force indicate that similar actions can seriously endanger balance of the support structure of some machine, and even, for example, can cause the main girder of the bridge crane to fall out. This and similar experiments allow us to formulate appropriate models of excitation loads by human force, which can then be used in simulation analyses in order to develop future systems of electronic protection of machines structures from adverse events.
Keywords: crowd load; dynamics; Fourier series; measurement; rhythmic load; vibration